SUELO ESTRUCTURAL-CU: UNA ACTUALIZACIÓN SOBRE SU USO EN EL AMBIENTE URBANO - Bassuk, N.L. (Agro Sur, 2007)
In 1995, I published the first scientific paper on what would become to be known as structural soil – later CU-Structural Soil. The development of this soil medium came about as we recognized that the single most important factor limiting the healthy growth of trees in urban areas was a lack of an adequate volume of soil. There appeared to be plenty of soil under sidewalk pavement and gravel for tree roots to grow into, however most of that soil was so highly compacted as to make it inaccessible to tree roots. The soil was too dense. So tree roots were contained within the hole into which they were planted, or managed to grow out of the hole into the gravelly base course directly under the paved surface- often heaving sidewalks in the process. Neither outcome was acceptable. Trees in sidewalk ‘containers’ grew poorly and never attained the envisioned size for which they were planted and tree roots that ‘broke out’ under the sidewalk often caused a tripping hazard as the pavement was raised.